Informal institutions and international business: Toward an integrative research agenda - Dau, Luis Alfonso; Chacar, Aya S.; Lyles, Marjorie A.; Li, Jiatao (Journal of International Business Studies, 2022)
This editorial introduces the literature on informal institutions and international business (IB) as well as the Special Issue. Informal institutions serve as the invisible threads that connect the fabric of social groupings, making them a critical element in the study of IB, but also especially challenging to capture both theoretically and empirically. As a result, there has been limited work on the topic, a lack of clarity on how to conceptualize and measure informal institutions, and a limited understanding of the role they play in IB. This editorial and Special Issue seek to address these gaps. Specifically, this editorial teases out the definitions of institutions, formal institutions, and informal institutions, and clarifies how they differ from organizations and culture. It then reviews the literature on the three main institutional traditions, explaining for each the role of informal institutions, and connecting them to the IB literature and Special Issue articles. Finally, it identifies gaps and proposes a future research agenda. The goal is to stimulate the academic conversation on the topic by showing how informal institutions are essential in studying international business.